An unusual cause of hemorrhagic shock: gastric Dieulafoy’s lesion - Erdoğan, Ahmet; Ferhatoğlu, Murat Ferhat; Pehlevan, Hikmet; Yıldırım, Osman; Şenol, Kazım (The European Research Journal, 2019)
Dieulafoy's lesion (DL) related massive gastrointestinal bleeding is a rare and mortal health condition. DL is a superficial vascular lesion of the gastric mucose that is mostly located in the proximal part of the stomach which is difficult to diagnose. Endoscopy is a safe and effective method for diagnosis and treatment. However, emergency surgery should be essential for diagnosis and treatment. Here we present a succesfull clinical and surgical management of a case with massive gastrointestinal bleeding related to gastric DL.